Increasing Teacher’s Professional Commitment Through Strengthening of Servant Leadership, Personality, Work Motivation, and Trust on Elementary School Teacher - Nurlaila, Hanik; Setyaningsih, Sri; Sunardi, Oding (The Islamic Education and Multiculturalism Foundation, 2024)
This research aimed to analyze the influence of servant leadership, personality, work motivation and trust on the professional commitment of elementary school teachers. The research, conducted in 157 accredited